Job Analysis Using Conventional and Precast Methods on Jalan Konggoasa Kendari City - Budiyono, Fardi; Hakiman; Sulaiman (International Journal of Management and Education in Human Development, 2022)
The increasing population growth of Kendari City demands the development of infrastructure development that continues to grow so that there must be road arrangements and systems irrigation or drainage network to avoid overflowing puddles on roads in Konggoasa Kendari City. Drainage is an infrastructure that functions to drain surface water to water receiving bodies and or to artificial infiltration structures. In other words, drainage has the meaning of draining, throwing or diverting water. The objectives of this study are: (1) to determine the cost comparison using the conventional method (cobblestone) and the precast method (u ditch). (2) to find out the comparison of time using the conventional method (cobblestone) and the precast method (u ditch). on the project implementation work on road Konggoasa Kendari City. The results of this study indicate that the work cost for the conventional method is IDR. 193.867.145 (One Hundred Ninety-Three Million Eight Hundred Sixty-Seven Thousand One Hundred Forty-Five Rupiah), and for the precast cost of IDR. 781.130.738 (Seven Hundred Eighty-One Million One Hundred Thirty Thousand Seven Hundred Thirty-Eight Rupiah), with the percentage of the cost of the conventional method being 75% cheaper than the precast method. And in terms of time for work using the conventional method for 66 days and for the precast method for 47 days with the percentage of time the precast method is 29% faster than the conventional method.